A new imperative of relationship between individual creativity and organisational innovation : a systematic review - Saharah Sapiyi; Nur Riza Mohd Suradi; Zainol Mustafa (Penerbit Universiti Kebangsaan Malaysia, 2022)
Innovation is imperative for competitiveness and works as a critical breakthrough determinant for organisations’ sustainable performance, while creativity functions as a catalyst for innovation processes or activities. One of the reasons for inadequate innovation is the lack of attention to creativity. Scholars have recently given a lot of attention to creativity by targeting individuals or employees but minimal systematic reviews were carried out on the correlation between organisational innovation and individual creativity. Hence, this article analysed the existing literature on the relationship between individual creativity and organisational innovation. We employed the PRISMA Statement (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) method of review, a methodical review of the Web of Science and Scopus repository and recognised 29 related studies. A more in-depth reviews of these articles produced five key themes and six sub-themes. We highlighted specific suggestions for attending more studies on qualitative methods and exploring more untapped determinants, moderating and mediating factors of individual creativity towards organisational innovation.